(untitled) (PANGEEA, 2025)
Abrud - The Golden City. The history of Abrud city has over 2000 years when is the capital of gold exploitation in the Apuseni Mountains. Gold mining was done in ancient times (dacs and romans), was resumed in the early Middle Ages (sec. 13) and continues until now. Gold mining has decisively influenced the life of the inhabitants of the area.. Gold operators have participated to the historical events related to this area: the revolt of Horea, Cloşca and Crişan, 1848 Revolution and the two world wars.